2002
DOI: 10.1124/jpet.102.036277
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Antagonists of Ethanol Inhibition of L1-Mediated Cell-Cell Adhesion

Abstract: Ethanol inhibits cell-cell adhesion mediated by the L1 cell adhesion molecule. 1-Octanol potently antagonizes this cellular action of ethanol and also prevents ethanol-induced dysmorphology and cell death in mouse whole embryo culture. NAPVSIPQ (NAP) and SALLRSIPA (SAL) are active peptide fragments of two neuroprotective proteins: activity-dependent neuroprotective protein and activity-dependent neurotrophic factor. NAP and SAL are neuroprotective at femtomolar concentrations against a variety of neurotoxins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…Indirect immunofluorescence with flow cytometry showed that D-NAP or L-NAP did not change the cell surface expression of L1 (data not shown). These results are consistent with previous data showing that the alcohol antagonists 1-octanol, 1-pentanol, and the peptides L-NAP and L-SAL do not modify L1 expression or adhesion (Wilkemeyer et al, 2000(Wilkemeyer et al, , 2002a.…”
Section: D-nap Is a Potent Ethanol Antagonist In L1-transfected Nih/3t3supporting
confidence: 83%
See 4 more Smart Citations
“…Indirect immunofluorescence with flow cytometry showed that D-NAP or L-NAP did not change the cell surface expression of L1 (data not shown). These results are consistent with previous data showing that the alcohol antagonists 1-octanol, 1-pentanol, and the peptides L-NAP and L-SAL do not modify L1 expression or adhesion (Wilkemeyer et al, 2000(Wilkemeyer et al, , 2002a.…”
Section: D-nap Is a Potent Ethanol Antagonist In L1-transfected Nih/3t3supporting
confidence: 83%
“…Cell adhesion was measured using a shortterm aggregation assay (Wilkemeyer et al, 2002a). Briefly, cells were detached and dissociated to single-cell suspension with calcium-and magnesium-free phosphate-buffered saline supplemented with 2 mM EDTA and 0.1 mg/ml DNase and diluted to 330,000 cells/ml for the NIH/3T3 cells and 250,000 cells/ml for the NG108-15 cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations